Hole‐Transporting Materials Based on Twisted Bimesitylenes for Stable Perovskite Solar Cells with High Efficiency. Issue 3 (15th January 2016) - Lin, Yan‐Duo; Ke, Bo‐Yu; Lee, Kun‐Mu; Chang, Sheng Hsiung; Wang, Kai‐Hung; Huang, Shih‐Han; Wu, Chun‐Guey; Chou, Po‐Ting; Jhulki, Samik; Moorthy, Jarugu Narasimha; Chang, Yuan Jay; Liau, Kang‐Ling; et al.
Abstract: A new class of hole‐transport materials (HTMs) based on the bimesitylene core designed for mesoporous perovskite solar cells is introduced. Devices fabricated using two of these derivatives yield higher open‐circuit voltage values than the commonly used spiro‐OMeTAD. Power conversion efficiency (PCE) values of up to 12.11 % are obtained in perovskite‐based devices using these new HTMs. The stability of the device made using the highest performing HTM (P1 ) is improved compared with spiro‐OMeTAD as evidenced through long‐term stability tests over 1000 h. Abstract : Stability trumps efficiency : Three hole‐transport materials based on a bimesitylene core presented, and their application in perovskite solar cells is evaluated. An overall power conversion efficiency of up to 12.11 % is achieved with these new materials and stability studies show that the long‐term stability of devices using the new materials is superior to commonly used spiro‐OMeTAD.